Someone else's husband : a novel - McCreight, Kimberly (Alfred A. Knopf, 2026)
"Gretchen Falk, a Park Avenue sophisticate born into great wealth and blessed with a storybook marriage, knows she lives a charmed life, and she's not about to risk losing any part of it. That's why she tried so hard to convince Richard, her devoted husband and father to their three children, not to join his old college friends on an expedition almost eight thousand miles away, to the legendary peak of Mount Kilimanjaro. Little did she know the beautiful artist climbing alongside him might prove the far bigger threat. Frankie Callahan's dream of artistic success is within reach, with her career-making exhibition at a celebrated New York gallery only weeks away. If all goes well, the show will leave her completely independent, free of the tainted money that ties her to a past - and a man - she's desperate to escape. To mark the end of this chapter, she is going to climb Kilimanjaro. But when she learns she's the sole female accompanying a group of longtime male friends, Frankie realizes that nothing about the trip will be as she expected. She certainly hasn't counted on meeting anyone like the very charismatic, very rich, very married Richard Falk. By the time the group descends - with one fewer than when they began - they have lost more than they ever could have imagined. Now, just two weeks after returning to New York, Frankie is dead, her East Village loft a blood-soaked crime scene. When Richard is charged in Frankie's death, it falls to Gretchen to piece together how the life she so carefully constructed could have imploded so completely. There are only two things she knows for sure: she's the only woman Richard has ever loved, and he would never hurt anyone. Someone Else's Husband is the sweeping and suspenseful story of two women on a collision course with love - and with each other - in which no one is right and everyone is very, very wrong"-- Provided by publisher.